Man who learnt to fly but could not land - Rajeevan, Thachom Poyil; Mathew, P. J. Tr. (Gurugram Hachette India, 2020)
K. T. N. Kottoor was activist, lover, communist, friend, saint, sinner - but, above all, he was a writer. . . Born into a family of rural wealth and near-feudal influence in a village nestled in British Malabar, Koyiloth Thazhe Narayanan Kottoor knows little of want. But as a patriotic fervour grips the country in the last decades of the Raj, a veritable avalanche of new ideas and ideals shapes the young KTN. As he grows from a boy who takes to writing not only as art but also as a tool of social change, to an activist enamoured of varying philosophies and enmeshed in India's freedom struggle, he grapples with hardship, love, lust and a search for meaning in a reality that forever disappoints. His is a tale both deeply personal and political - tracing a web of caste, sexuality and ideology, while also navigating the struggles of a man coming to terms with himself as a writer and as an individual. Award-winning author Thachom Poyil Rajeevan weaves a magical almost-biography of a fictional writer, one inhabited by goddesses and ghosts, a fortune-telling parrot, dead humans in the avatar of crows, and a blind woman who hears - and sees - better than anyone else. Masterfully translated from the original Malayalam, The Man Who Learnt to Fly but Could Not Land is a poignant exploration of the power of writing, the chaos of a country's rebirth and the life of an idealist caught up in the maelstrom.
Keywords: English Fiction; Biography